Optimal control of a high gain DC- DC converter - Lopamudra Mitra; Ullash Kumar Rout (Institute of Advanced Engineering and Science, 2022)
Different types of power conditioning systems are mostly used with renewable energy systems. As the output of solar photovoltaic (PV) is low high voltage converters are required. These converters can be used for both standalone and grid tied systems. A high voltage gain DC-DC converter is proposed which can be used with photovoltaic modules to get high output voltage. This converter can provide a high voltage gain and a proportional integral derivative (PID) controller is used to maintain the high output voltage of the proposed converter coupled with solar photovoltaic module. The PID controller is first designed using classical Ziegler Nichol’s method (ZN) and optimal control of the converter is obtained by using different optimisation methods like particle swarm optimisation (PSO), bacteria foraging algorithm (BFA) and its comparison is presented in this paper.